(untitled) (Journal of the Society for Musicology in Ireland, 2018)
A review of Tilly Fleischmann, Tradition and Craft in Piano-Playing, edited by Ruth Fleischmann and John Buckley (Dublin: Carysfort Press, 2014), ISBN 978-1-909325-53-1.